Transition metal complexes containing a ditopic redox active ligand featuring very intense visible absorption bands. (December 2015) - Bonanno, Nico M.; Van Damme, Natasha; Lough, Alan J.; Lemaire, Martin T.
Abstract: The preparation and structural properties of a new ditopic redox active arylazo ligand 10-[6-(10-hydroxy-9-phenanthrylazo)-4-pyrimidinylazo]-9-phenanthrol is described along with the electronic and magnetic properties of nickel(2+) and manganese(2+) complexes containing this ligand. Spectroscopic and structural data support the formation of tetranuclear grid-type [2 × 2] complexes for the transition metal complexes, which would mark the first examples of such complexes with redox active arylazo ligands; however, one dimensional coordination polymers are another possible structural interpretation. In any case, the electronic spectrum of each complex exhibits extremely intense visible absorption bands, which are particularly strong in the nickel complex. These lower energy absorptions result from transitions between frontier molecular orbitals that are nearly completely ligand in character as suggested by density functional theory calculations. The nickel complex features rich cathodic electrochemical behavior resulting from the reduction of the multiple azo groups present in this material. Graphical abstract: We describe the synthesis and structural properties of a new ditopic arylazo ligand as well as the synthesis, structure and electronic properties of polynuclear nickel(II) or manganese(II) complexes containing this ligand. Of note, we observe intense visible absorption bands with very large molar absorptivities in these complexes, which results from low energy HOMO-LUMO type transitions as supported by calculations from density functional theory calculations. Highlights: Synthesis of a new ditopic arylazo redox active ligand. First reported possible grid-type complexes containing arylazo redox active ligands. Ligand centered electronic transitions with very high molar absorptivities.